PERBEDAAN QIRA’AT DAN PENGARUHNYA DALAM ISTINBATH HUKUM - Halimah B (Al-Risalah, 2019)
Qira'at is a school that is held by a qira'at priest who is different from the others in the pronunciation of the lafaz-lafaz al-Qur'an, and agrees with the narrations and paths thereof, both differences in the pronunciation of letters, the alms and the pronunciation of the shape.Qira'at al-Qur'an is tawqify, which is sourced from the Messenger of Allah. not ijtihadi. The scholars set criteria as a standard for accepting the validity of the reading, that must be in accordance with the rules of Arabic, in accordance with the writing of one of the mani Usmani manuscripts and narrated with a valid sanad. On this basis the ulama concludes 6 (six) qira'at levels; namely: qira'at muatawatir, masyhur, ahad, syaz, muwdhu and mudraj.The difference in qira'at does not always lead to changes in the meaning it contains. Likewise, in legal matters, it sometimes affects legal differences and sometimes does not affect the differences in the law imposed.